WEBSITE-BASED IMPLEMENTATION IN INFORMATION SYSTEMS FOR SUPERVISORY MANAGEMENT PURPOSES - Fanada, Ayudhia Isnafiani; Nurgiyatna, Nurgiyatna (STKIP PGRI Tulungagung, 2024)
Website-based implementation of Supervisory Management Information Systems at Inspektorat Daerah Kabupaten Karanganyar is very important in the supervision process for audit reports. Supervision of employee performance that is usually carried out is less effective if it is done physically because it wastes too much time and still uses paper. The purpose of this study is to implement a website-based Supervisory Management Information System, so that employee performance in the audit reporting process can run efficiently and audit reports can be stored directly in the database system. This system is designed using a website-based application with the CodeIgniter framework. The process of designing this system uses the Software Development Life Cycle (SDLC) stages with the Waterfall method. At the end of the stage, testing is carried out using Black Box Testing and calculating the value of the System Usability Scale (SUS). The results of the Black Box Testing show that the system works perfectly. In the SUS calculation, from 36 Respondents who were inspectorate employees, the average score was 71.86. This shows that this system can be easily used and managed by Inspektorat Daerah Kabupaten Karanganyar.